Supporting Hydropower : An Overview of the World Bank Group's Engagement - Rex, William; Foster, Vivien; Lyon, Kimberly; Bucknall, Julia; Liden, Rikard (World Bank Group, Washington, DC, 2014)
Hydropower development makes an essential contribution to reducing poverty, boosting shared prosperity, and improving sustainability. Water storage associated with some hydropower projects can also make important contributions to water and food security and to climate resilience. The World Bank Group (WBG) thus uses multiple instruments to support sustainable and responsible hydropower projects of various sizes and types, depending on local need. But hydropower can also carry significant risks that must be carefully managed. Supporting sustainable hydropower is important for the World Bank Group, because hydropower potential exists where electricity is most needed. Hydropower production is the least-cost method of providing electricity in many developing countries. The WBG is committed to helping its clients continuously improve the way they approach hydropower so as to better manage its risks and better share the benefits of this renewable resource. Support for hydropower helps manage risks and can yield local, national, regional, and global benefits. Sustainable hydropower has three dimensions: physical, financial, and social/environmental. While a large amount of progress has been made on sustainability, particularly over the last decade, new challenges continue to emerge or become more pressing. These include: 1) securing multiple benefits from investments in hydropower; 2) managing cascades of projects to optimize additional benefits or to prevent exacerbating negative impacts; and 3) developing a more sophisticated understanding of land and water interactions.